Полювання на птахів на східних теренах Речі Посполитої у світлі наративних джерел ХVІ–ХVІІ століття - Кравченко, Н. (Київський національний університет імені Тараса Шевченка, 2022)
Проаналізовано практики полювання на птахів у Речі Посполитій у світлі трактатів та щоденників. Залежно від їхньої тематики полювання на птахів та ловецтво в них репрезентовані сповна чи, навпаки, фрагментарно. Ці джерела становлять інтерес з огляду на наявність у них даних, що дають можливість вивчити тогочасний технічний рівень розвитку мисливства, полювання як частину повсякдення того часу і, власне, його культурну складову. Ці дані, за умов мінімальної інформації щодо руських теренів Речі Посполитої, можуть бути частково екстрапольовані й на українське мисливство ранньомодерного часу. Період, який проаналізовано у статті, цікавий з погляду накопичення знань про орнітофауну, рекомендації часових обмежень полювання на період розмноження. Друге є виявом прагматичного ставлення до цього ресурсу, усвідомлення його цінності, що водночас можна трактувати як первинний вияв екологічної свідомості.

The article analyzes bird hunting in the Polish-Lithuanian Commonwealth in the light of such sources as treatises and diaries; some of them have also left their impression on the history of literature. Depending on their subject, hunting as such or merely bird hunting (as its branch) are represented completely or fragmentarily in these sources. Owing to hunting treatises as the main source in the context of this study, it is possible to reconstruct the technical level of development in this area at the time mentioned. These sources are relevant in terms of researching the knowledge about avifauna of the time, habits of its representatives, behavior, breeding season (during that period it was recommended to limit hunting). The latter is a manifestation of a pragmatic attitude to this resource, awareness of its value, which can also be interpreted as a primary manifestation of environmental awareness. A small number of the analyzed sources relate to the Ukrainian lands in particular. However, due to the similarity of landscapes and the conservatism of hunting practices, Polish examples can sometimes be illustrative. In the memoirs of this period hunting is represented from a different angle than that of the treatises – as part of everyday life at that time. Given that hunting chase was considered the best way for elites to hunt as a form of military training, bird hunting was inconspicuous. It was often a craft of poor servants, so it is visible in diaries from another angle – as a source of new gastronomic experiences. Most often we are talking about baked partridges and blackbirds, capercaillie, bustard, quail, etc.; the use of smaller birds is known mainly due to rare mentions. In the diaries, dedicated to the diplomatic missions to other countries and diplomatic receptions, the birds of prey, along with expensive sable furs can often be found in the lists of prestigious gifts. A spin-off manifestation of the popularity of hunting was the emergence of hunting sayings.
Bird Hunting in the Eastern Part of the Commonwealth in the Light of Narrative Sources of the 16th – 17th Centuries
Keywords: наративні джерела; мисливство; полювання; птахи; Річ Посполита; ХVІ–ХVІІ століття; narrative sources; hunting; shooting; birds; Polish-Lithuanian Commonwealth; 16th – 17th centuries